Development of Air Pollutants Emission Inventories for Ships around Japan on a High Geographical Resolution - Tatsuya Sakurai; Miu Ito; Shinichi Hanayama (Asian Journal of Atmospheric Environment, 2021)
Abstract This study developed a database of emission inventories from ships around Japan using the activity data in the 2015 Japanese fiscal year. The emission of air pollutants from ships was estimated for fuel combustion in main engine, auxiliary engines, and boilers onboard. The ships’ operations for the emission estimation in the exhaust gas consist of ships in navigation, ships at anchor, and fishing boats. For the emission estimation regarding navigation ships, data from Automatic Identification System (AIS) received at the stationary stations on land in Japan were used in this study to calculate the activity. The emission amounts were compared between the sea (Seto Inland Sea (SIS) and Tokyo Bay) and prefectures surrounding those ocean areas. The ship emission ratios in total anthropogenic emissions including the land part reached SO2: 29%, PM: 40%, and NOx: 22% for the SIS area. In Tokyo Bay, the ship emission ratios in total reached SO2: 36%, PM: 28%, and NOx: 13%, and the emission intensities per unit area for SO2 and PM2.5 are approximately three times higher than those in the other regions, respectively. Therefore, the shipping traffic density is relatively higher compared to transportation on land, and the emission is condensed locally. Assuming that the 2020 global sulphur limit switched to a sulphur content of 0.50% m/m, SO2 emissions could be reduced to 24% in SIS and 22% in Tokyo Bay, sulphate emissions could be reduced to 23% in SIS and 21% in Tokyo Bay, and PM emissions could be reduced to 39% in SIS and 36% in Tokyo Bay. Therefore, the 2020 global sulphur limit should reduce the emission from ships around the Japan coastal area and improve the air quality in congested water areas such as SIS and Tokyo Bay.